1997
DOI: 10.3758/bf03199088
|View full text |Cite
|
Sign up to set email alerts
|

Retention of conditioned autonomic and behavioral responses in preweanling rats: Forgetting and reinstatement

Abstract: Preweanling rats, 16days of age, responded to an olfactory conditioned stimulus (CS) paired with a shock unconditioned stimulus (US) with increases in heart rate and behavioral activation. In two experiments this finding was replicated and, in addition, it was found that the form of these conditioned responses (CRs) changed after a retention interval, Whentested 24 h after CS-USpairings, the subjects displayed a decrease in heart rate accompanied by CS-elicitedfreezing. Givingtwo unsignaled shocks prior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Although long training-test intervals often result in attenuated performance through forgetting, short intervals can actually lead to an improvement in conditioned responding (e.g., McMichael, 1966;Randich & Rescorla, 1981;Rudy & Morledge, 1994;Tarpy, 1966). Furthermore, recent research has suggested that the interval between training and test may influence the directional characteristics of cardiac and behavioral CRs in the preweanling rat (Hunt, 1997). In addition, some investigators have reported that the strength of the learned response may actually increase following a delay between training and testing in younger organisms (Boller, Rovee-Collier, Borovsky, O'Connor, & Shyi, 1990;Fagan & Rovee-Collier, 1983;McKinzie, Chen, & Spear, 1998).…”
mentioning
confidence: 99%
“…Although long training-test intervals often result in attenuated performance through forgetting, short intervals can actually lead to an improvement in conditioned responding (e.g., McMichael, 1966;Randich & Rescorla, 1981;Rudy & Morledge, 1994;Tarpy, 1966). Furthermore, recent research has suggested that the interval between training and test may influence the directional characteristics of cardiac and behavioral CRs in the preweanling rat (Hunt, 1997). In addition, some investigators have reported that the strength of the learned response may actually increase following a delay between training and testing in younger organisms (Boller, Rovee-Collier, Borovsky, O'Connor, & Shyi, 1990;Fagan & Rovee-Collier, 1983;McKinzie, Chen, & Spear, 1998).…”
mentioning
confidence: 99%
“…It is characteristic to present several startle stimuli prior to the explicit CS-startle test trials when testing for fear-potentiated startle (Davis, 1984; see also Experiment 1). Furthermore, it has been shown that exposure to a noxious stimulus (e.g., shock) can interfere with the expression of conditioned fear under some circumstances (e.g., Hunt, 1997;Hunt et al, 1998;Randich & Rescorla, 1981). The results of Experiment 2a indicated that presentation of pretest startle stimuli failed to have an observable effect on the CS's ability to elicit a conditioned cardiac response.…”
Section: Discussionmentioning
confidence: 69%
“…More recently, it has become clear that an explicit retention interval is sometimes critical for response expression in preweanling subjects (e.g., Hunt, 1997;Hunt, Hess, & Campbell, 1998;McKinzie, Chen, & Spear, 1998). For example, Hunt et al (1998) observed that a conditioned decrease in heart rate to a light previously paired with footshock was expressed by animals as early in development as a conditioned freezing response, provided there was a brief interval of time (2 -24 hr) separating the conditioning episode from the test session.…”
mentioning
confidence: 99%
“…Changes in heart rate have been widely used as a measure of both unlearned and acquired fear (for reviews see Hunt and Campbell 1997b;Schneiderman 1987). Autonomic responses often covary with behavioral measures of conditioned fear, including behavioral immobility (freezing) and fear-potentiated startle (Hunt 1997a;Hunt et al 1997c;Whalen and Kapp 1991). While there is a paucity of teratological research employing measures of autonomic nervous system function, there are a few reports suggesting that autonomic control may be sensitive to perinatal drug and toxin exposure Heyser et al 1994;Mactutus 1999) and other early life environmental manipulations (Card et al 2005;Hofer 1981).…”
mentioning
confidence: 96%